Confirmatory Factor Analysis of Conflict Management Instruments for Muhammadiyah High School Students - Salsabila Maharani Irsa Putri; Mustaqim Setyo Ariyanto; Agus Salim (INDONESIAN COUNSELING AND PSYCHOLOGY, 2025)
This study aims to develop and evaluate the validity and reliability of a conflict management scale specifically designed for students of Muhammadiyah senior high schools in Yogyakarta City. The development process began with constructing indicators based on Robbins and Judge’s five dimensions competition, collaboration, avoidance, accommodation, and compromise followed by content validation by nine experts using Aiken’s V. The analysis produced V values ranging from 0.638 to 0.972 (>0.50), indicating that all items were suitable for further testing. The scale was then administered to 363 students aged 14–19 years from seven Muhammadiyah senior high schools. Participants were selected through purposive sampling based on the criteria of being active students in grades X, XI, and XII. Data were analyzed using Confirmatory Factor Analysis (CFA) with LISREL to verify the factor structure. The results demonstrated good model fit (χ²/df = 1.24; RMSEA = 0.028; GFI = 0.92; AGFI = 0.90; CFI = 0.99). Construct reliability was achieved, with Composite Reliability values ranging from 0.840 to 0.890 and Average Variance Extracted values above 0.50 across all dimensions. Descriptive findings showed that accommodation was the most dominant conflict management style among students. Overall, the scale is valid, reliable, and suitable for psychological assessment and for supporting character education programs in schools. These findings guide readers to consider how conflict management patterns shape student character development in educational settings.